The effectiveness of Madrasah Head Leadership Management at MAN 1 Sungai Penuh - Eka Putra (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2023)
Abstract: The effectiveness of Madrasah Head Leadership Management at MAN 1 Sungai PenuhThe quality of a madrasah always reflects the quality of the madrasah environment, because the madrasah head has a great influence in efforts to improve educational standards. The quality of a school is the sum of its inputs, procedures and outputs. Both learning processes and inputs are determined by the quality of accessible resources. There is a correlation between the output of a madrasah and its efficiency. The purpose of this article is to analyze how the madrasah head succeeds in improving the quality of his institution by utilizing all the resources he has. The method used in this research is qualitative. The research location is MAN 1 Sungai. Primary and secondary resources are used by researchers in data collection. The data analysis that researchers use is qualitative data analysis in an interactive way. Research results reveal that overall MAN 1 Sungai Penuh organizes quality education. This is evident in the way the school administration and faculty members carry out their responsibilities as professional staff members, ensuring that students receive a rigorous and engaging education. the research conclusion shows that effective leadership and management at MAN 1 Sungai Penuh is an indicator of the high competence of the madrasah head.Abstrak: Efektivitas Manajemen Kepemimpinan Kepala Madrasah DI MAN 1 Sungai PenuhMutu suatu madrasah selalu mencerminkan mutu lingkungan madrasah, karena kepala madrasah mempunyai pengaruh besar dalam upaya peningkatan standar pendidikan. Mutu suatu sekolah merupakan penjumlahan dari masukan, prosedur, dan keluarannya. Baik proses maupun masukan pembelajaran ditentukan oleh kualitas sumber daya yang dapat diakses. Ada korelasi antara output madrasah dan efisiensinya. Tujuan artikel ini adalah untuk menganalisis bagaimana kepala madrasah berhasil meningkatkan kualitas lembaganya dengan memanfaatkan seluruh sumber daya yang dimilikinya. Metode yang digunakan dalam penelitian ini adalah kualitatif. Lokasi penelitian adalah MAN 1 Sungai. Sumber daya primer dan sekunder digunakan peneliti dalam pengumpulan data. Analisis data yang peneliti gunakan adalah analisis data kualitatif dengan cara interaktif. Hasil Penelitian mengungkap bahwa Secara keseluruhan MAN 1 Sungai Penuh menyelenggarakan pendidikan yang berkualitas. Hal ini terbukti dalam cara administrasi sekolah dan anggota fakultas melaksanakan tanggung jawab mereka sebagai anggota staf profesional, memastikan bahwa siswa menerima pendidikan yang ketat dan menarik. Kesimpulan penelitian menunjukkan bahwa kepemimpinan dan pengelolaan yang efektif di MAN 1 Sungai Penuh merupakan indikator tingginya kompetensi kepala madrasah.